BUDAYA SEBAGAI STRATEGI DAKWAH (STUDI KASUS BUDAYA KENDURI MASYARAKAT JAWA DESA SIJAMBI) - Dodi Candra; M. Joharis; Zulkifli Zulkifli (Universitas Pahlawan Tuanku Tambusai, 2022)
The emergence of religion makes ancestral traditions used as a medium for delivering da'wah messages. When Islam entered the archipelago, the kenduri tradition was used as a medium of da'wah in conveying Islamic messages, because the kenduri tradition was very strong in society. Therefore, in this study, researchers tried to explore how the kenduri tradition became a medium of da'wah in spreading Islamic teachings in Javanese society. The method used in this study is a qualitative method with a descriptive approach. The data collection technique was carried out by means of a study library by finding studies related to culture as a propaganda strategy, case studies of Javanese Kenduri culture, as well as observation by directly observing the kenduri procession in Sijambi Village. The results of the study show that there are four da'wah messages in the death feast tradition of Sijambi village. First, the verbal delivery of da'wah messages in the death feast tradition is found in the procession of reading tayyibah sentences, tasbih, dhikr and prayer readings. Second, the delivery of da'wah messages through nonverbal language. Third, the provision of food and drink is intended as a form of alms from the deceased in the hope of blessing from Allah SWT. Fourth, the da'wah messages contained in the Kenduri tradition of the Sijambi Village community are the values ​​of unity and friendship between fellow communities. Keywords : Culture, Da'wah, Kenduri